The effects of self-compassion on daily emotion regulation and performance rebound among college athletes: Comparisons with confidence, grit, and hope. (January 2022) - Doorley, James D.; Kashdan, Todd B.; Weppner, Caroline H.; Glass, Carol R.
Abstract: Self-compassion (SC) facilitates healthy responses to stressful events among athletes. Existing findings are predominantly retrospective, however, and questions remain about the role of SC in college athletes' daily emotion regulation and sport performance. Sixty-seven college athletes completed daily diaries for 14 consecutive days during their competitive seasons. We tested whether SC predicted 1) emotion regulation strategy use and effectiveness following negative events and 2) sport performance rebound following subjectively poor performances the previous day. We also compared the effects of SC with grit, sport-specific hope, and sport-related self-confidence, each in separate models. Results showed that SC and sport-specific hope predicted greater use of cognitive reappraisal in response to negative events. Interestingly, social support seeking was associated with higher negative emotions on average. However, higher levels of SC, grit, and sport-specific hope (but not sport self-confidence) mitigated this association. When athletes' subjective performance during practice fell 1 SD below their two-week mean, SC, grit, and sport-specific hope predicted improved subjective performance during the next day's practice by 7.8–10.9%. Sport confidence had no effect, suggesting that coaches and sport psychology consultants might consider shifting their focus toward cultivating SC instead. Highlights: We compared self-compassion to other positive traits in athletes' daily lives Self-compassion and hope predicted greater daily cognitive reappraisal Self-compassion predicted enhanced subjective performance after poor performances Similar effects emerged for grit and hope but not sport self-confidence Self-compassion, like grit and hope, may help athletes function optimally despite distress